Implementasi Model Pembelajaran Sentra dalam Meningkatkan Kemandirian Anak di RA Zahrotun Nisa - Rosmina, Rosmina; Susanti, Reni; Dewi, Resti Sulistia (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to enhance children’s creativity through play-based methods at RA Zahrotun Nisa. Creativity is a crucial aspect of early childhood development, which can be fostered through well-structured and innovative play activities. This research employs classroom action research (CAR) using the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The subjects of this study were 20 students from Group B at RA Zahrotun Nisa. Data collection techniques included observation, interviews, and documentation. The findings indicate that the gradual implementation of play-based methods effectively enhances children’s creativity, as evidenced by improvements in divergent thinking skills, imagination, and problem-solving abilities. In the first cycle, only 55% of children showed increased creativity, but this figure rose to 85% in the second cycle. These results confirm that well-designed play-based learning strategies positively contribute to children’s creative development. Therefore, it is recommended that educators at RA Zahrotun Nisa continue to develop play-based learning strategies to maximize children’s potential.